PREVALENSI ANAK BERKESULITAN BELAJAR DI SEKOLAH DASAR SE KECAMATAN PAUH PADANG - Fitria - Masroza (Jurnal Penelitian Pendidikan Khusus, 2013)
Abstract This research background of differences in perception or perspective teachers of children who have behavioral disorders in the learning process at Junior High School 24 in Padang. The purpose of this study was to obtain an overview of teachers' perceptions of children who have behavioral disorders behavioral  disorder   include  the  presence  of  children  in  school,  social interaction  with  the  teacher's  behavior,  social  interaction  with  peers  and learning achievement of children  behavioral disorders. The methodology of this research is descriptive quantitative  approach. From the results of this study indicated that most of the teachers noticed the presence, interaction and interpretation of behavior in children at Junior High School 24 in Padang.